Manajemen Pendidikan Karakter di SMP Swasta Islam Jamiah Al-Aziziyah Batee Iliek - Puteh, Tarmizi (Ameena Journal, 2023)
Character education plays a crucial role in shaping the younger generation with integrity and competitiveness. One of the educational institutions strongly committed to implementing character education is the Private Islamic Junior High School Jamiah Al-Aziziyah in Batee Iliek, Aceh. This article elucidates how character education management is implemented in this school, focusing on principles, strategies, and resulting impacts. The research method employed in this study is literature review. The findings of this study reveal that: Private Islamic Junior High School Jamiah Al-Aziziyah Batee Iliek serves as an inspirational example of how character education management can be effectively implemented. Adhering to strong principles and well-planned strategies, the school has created an educational environment capable of shaping students who are not only academically adept but also possess strong characters rooted in Islamic values. The positive impact of this character education can be observed in students' daily behaviors. Thus, Private Islamic Junior High School Jamiah Al-Aziziyah Batee Iliek has substantiated that character education is not merely a concept but a reality capable of shaping a better future.